Marginal Integrity of Turkom-Cera compared to other All-ceramic materials: effect of finish line - Al-Makramani, B.M.A.; Razak, A.A.A.; Abu-Hassan, M.I.; Sulaiman, E.; Loon, L.J.; Yahya, N.A. (2011)
The aim of this study was to evaluate the marginal adaptation of Turkom-Cera all-ceramic crowns compared to In-Ceram and Procera AllCeram systems. The influence of finish line design (chamfer or shoulder) on the marginal adaptation of Turkom-Cera all-ceramic crowns was also investigated. Thirty human premolars were prepared with chamfer margins and assigned to either the Turkom-Cera, In-Ceram, or Procera system group. In addition, 10 premolars were prepared with rounded shoulder finish lines and assigned to an additional Turkom-Cera group. Ceramic copings (0.6-mm thick) were fabricated for each group following the manufacturers' instructions. The copings were seated on abutments using a special holding device that facilitated uniform loading, and marginal adaptation was assessed using a stereomicroscope. Data were analyzed using analysis of variance, the Tukey HSD post hoc test, and an independent samples t test. There was a statistically significant difference regarding marginal adaptation among the three all-ceramic systems (P < .05). There were no significant differences in the mean marginal discrepancies of Turkom-Cera crowns among chamfer and shoulder finish line groups (P > .05). Within the limitations of this study, the marginal discrepancies were all within the clinically acceptable standard. Int J Prosthodont 2011;24:379-381.